Entrapment enhancement of peptide drugs in niosomes - Manosroi A. (2014)
The objective of this study was to enhance the entrapment of various charged peptide drugs [(bacitracin (BCT), insulin and bovine serum albumin (BSA)] in niosomes by modifying the vesicular charge compositions. Cationic, anionic and neutral niosomes were prepared from sorbitan monostearate (Span 60) or polyoxyethylene sorbitan monostearate (Tween 61), cholesterol (CHL), dimethyldioctadecylammonium bromide (DDAB) and/or dicetyl phosphate (DP) in distilled water, by freeze dried empty liposome (FDEL) method. Morphology and vesicular sizes of the vesicles were investigated by optical microscope, TEM, X-ray diffractometry and dynamic light scattering. The entrapment efficiency of the peptides in niosomes was determined by gel electrophoresis and gel documentation. After reconstitution of the empty niosomal powder in phosphate buffer pH 7.0 containing the peptide drugs, they were oligolamellar membrane structure, with the sizes of 40-60 nm, except the neutral niosomes entrapped with insulin and cationic niosomes entrapped with BSA which showed the sizes of 0.1-1.3 μm and 100-150 nm, respectively. The zeta potential values of neutral, cationic and anionic niosomes entrapped with BSA, insulin and BCT were -22.3±1.52, -30.7±2.92 and ±22.68±1.31 mV, respectively. The entrapment efficiency of BSA, BCT and insulin in neutral niosomes (Tween 61/CHL at 1 : 1 molar ratio) was 72.94, 69.89 and 10.26%, in cationic niosomes (Tween 61/CHL/DDAB at 1 : 1 : 0.05 molar ratio) was 84.54, 32.85 and 87.15% and in anionic niosomes (Tween 61/CHL/DP at 1 : 1 : 0.05 molar ratio) was 50.13, 90.88 and 44.31%, respectively. The highest entrapment efficiency of BSA, BCT and insulin at 72.94, 90.88 and 87.15 was observed in neutral, anionic and cationic niosomes, respectively. The results from this study has suggested the appropriate niosomal formulation to entrap the peptides with different charges and polarity for pharmaceutical application. © 2010 Informa UK Ltd.